Natural history of therapeutic management in oral cancer - Mohapatra, S C; Srivastava, V K; Mohapatra, P; Gupta, J NP; Tandon, J (Indian Journal of Community Health, 1995)
The natural history of a diseases is greatly influenced by the course of therapeutic management. Just after the tissue stage of the disease is aver. The cure rate of diseases, particularly those of cancers, could probably be modified to a greater extent, if the natural history of the therapeutic management is understood properly, so that the community education programme be organised in the proper direction, to trigger early diagnosis. Home remedy urn the first preference of 76.8% of oral cancer cases, 64.6% preferred traditional unqualified practitioners as their 2nd preference of place of treatment for oral cancer. Thus during the stage of fa stigium a case oj oral cancer gets frustrated with the hospital treatment and awaits death counting his days